Treatment of the acquired syphilis with azithromycin - Passos, Mauro R.L.; Goulart Filho, Rubem A.; Carvalho, Altamiro, V.V.; Barreto, Nero A.; Nascimento, Auri V.S.; Varella, Renata Q.; Pinheiro, Vandira M.S.; Tavares, Rogério R.; Santos, Cláudio C.C.; Azevedo, Patrícia M.C. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Introduction: Syphilis is a highly prevalent STD throughout the world, specially affecting countries with socioeconomic problems. The disease defies medicine, being a problem even in developed countries. There are few studies comparing different therapies. In the last years, many studies about the use of azithromycin in syphilis have shown excellent cure rates. Objective: To evaluate the effficacy of azithromycin in the treatment of acquired syphilis in patients with any impediments to the use of penicillin G benzathine. Methods: An open study, in one center, the STD Sector of the Universidade Federal Fluminense in Niteroi, Rio de Janeiro, from 1997 to 2000. 57 patients with early syphilis (primary/ second ary and with early latent syphilis were followed the syphilis diagnostic was made with dark-field bacterioscopy and/or V.D.R.L. serology. The serological follow-up was made bimonthly. The patients were assigned to two groups: A. 1g of azitrromycin/week for 3 weeks; B. 1g of azthromycin/week for 4 weeks. The criteria for cure were the remission of the symptoms and signs of the disease and a fourt gold decline in the serology titers after treatment relative to the pre-treatment values or serological negativation. Results: All patients presented genital and/or dermatological lesion, and 50 out of 57 evolved with clearance of the lesion in two weeks. No important secondary effects or hipersensibility reactions to the drug were seen. Cure rate for group A (3 doses) was 27/27 (100%); for group B (4 doses) was 28/30 (93,4%), a total of 55/57 (96,7%), with no statistically significant difference between the two groups. Associated illnesses were 6/57 (10,5%) HIV positivity, 5/57 (8,8%) HPV lesions, 5/57 (8,8%) candidiasis, 2/57 (3,5%) trichomoniasis and 1/5 (1,8%) canchroid. The Jarisch-Herxheimer reaction occurred in 3 patients. Conclusion: The experience gathered at the STD Sector of the UFF allows one to conclude that azithromycin may be used as a practical, safe and efficacious treatment for acquired syphilis for patients in early recent and early latent phases.